3D printed step‐gradient composite hydrogels for directed migration and osteogenic differentiation of human bone marrow‐derived mesenchymal stem cells. Issue 2 (25th June 2021) - Motealleh, Andisheh; Schulten, Alicia; Kehr, Nermin S.
Abstract: With the aid of a 3D printing technique, we create a 3D printed step‐gradient (nano)composite scaffold (GradS). GradS is generated by spatially connecting different (nano)composite hydrogel precursors varying in their concentrations of GelMA, alginate, and functional nanomaterials [ Dex PMO‐PDL = dexamethasone (Dex)‐ and poly‐ d ‐lysine (PDL)‐functionalized periodic mesoporous organosilicas (PMO)]. GradS not only allows for improving the viability of human bone marrow‐derived mesenchymal stem cells (hBM MSC), but GradS is also applied to direct the migration of hBM MSC toward the higher concentration of GelMA and nanomaterials (NMs) within the 3D gradient porous hydrogel network. Furthermore, we demonstrate that the osteogenic differentiation capacity of hBM MSC is promoted by an increase in the content of GelMA and Dex PMO‐PDL; increasing concentrations of GelMA and Dex PMO‐PDL within the GradS regulates the migration and subsequent osteogenic differentiation of hBM MSC within the 3D gradient hydrogel network. Abstract : 3D printed step‐gradient (nano)composite scaffold (GradS) is reported. GradS allow us to influence the viability, migration and osteogenic differentiation of hBM MSC. The GelMA and Dex PMO‐PDL concentration‐dependent migration and subsequent osteogenic differentiation of hBM MSC in the GradS is shown.